Differential Expression of Serum TUG1, LINC00657, miR-9, and miR-106a in Diabetic Patients With and Without Ischemic Stroke - Abdelaleem, Omayma O; Shaker, Olfat G.; Mohamed, Mohamed M.; Ahmed, Tarek I.; Elkhateeb, Ahmed F.; Abdelghaffar, Noha K.; Ahmed, Naglaa A.; Khalefa, Abeer A.; Hemeda, Nada F.; Mahmoud, Rania H. (Frontiers in Molecular Biosciences, 2022)
Background: Ischemic stroke is one of the serious complications of diabetes. Non coding RNAs are established as promising biomarkers for diabetes as well as its complications. The present research investigated the expression profiles of serum TUG1, LINC00657, miR-9 and miR-106a in diabetic patients with and without stroke. Methods: A total of 75 diabetic patients without stroke, 77 patients with stroke as well as 71 healthy controls were recruited in the current study. The serum expression levels of TUG1, LINC00657, miR-9 and miR-106a were assessed using quantitative real-time polymerase chain reaction assays. Results: We observed significant high expression levels of LINC00657 and miR-9 in serum of diabetic patients without stroke comparing to control participants. At the same time, we found marked increase of serum TUG1, LINC00657 and miR-9 as well as marked decrease of serum miR-106a in diabetic patients who had stroke relative to those without stroke. Also, we revealed positive correlation between each of TUG1, LINC00657 as well as miR-9 and National Institutes of Health Stroke Scale (NIHSS). However, there was negative correlation between miR-106a and NIHSS. Finally, we demonstrated negative correlation between LINC00657 and miR-106a in diabetic patients with stroke. Conclusion: serum non coding RNAs, TUG1, LINC00657, miR-9 and miR-106a display potential to be novel molecular biomarkers for diabetes complicated with stoke , suggesting that they might be new therapeutic targets for treating diabetic patients with stroke.